Maternal obesity and intrapartum obstetric complications among pregnant women: Retrospective cohort analysis from medical birth registry in Northern Tanzania. (13th January 2020) - Mwanamsangu, Amasha H.; Mahande, Michael J.; Mazuguni, Festo S.; Bishanga, Dunstan R.; Mazuguni, Nickolas; Msuya, Sia E.; Mosha, Dominic
Summary: Background: In the last decade, Tanzania has observed a dramatic increase in overweight and obesity among women of childbearing age, a demographic shift that has been associated with intrapartum obstetric complications in high‐income countries. Similar increases in maternal morbidity including postpartum haemorrhage, hypertensive disorders of pregnancy, and rates of caesarean delivery have not yet documented in Tanzania. This analysis describes intrapartum obstetric complications associated with maternal obesity among pregnant women delivering at teaching hospital in Northern Tanzania. Methods: A retrospective cohort analysis was conducted using the hospital's antenatal care (ANC) and birth registries from 2000 to 2015. The World Health Organization (WHO) body mass index (BMI) categories were applied to classify BMI status of pregnant women within 16 weeks of gestational age at their first ANC visit. Relative risk (RR) of obstetric complications with corresponding 95% confidence intervals (CIs) were estimated using multivariable log‐binomial regression, adjusting for clustering effect for the correlation between multiple deliveries of the same woman. Results: Among 11 873 women who delivered babies in the hospital during the study period, 3139 (26.5%) fit the definition of overweight and 1464 (12.3%) women with obesity. Compared with women with normal weight, women with obesity were at over 2.6 times at risks of experiencing pre‐eclampsia/eclampsia (RR: 2.66; 95% CI, 2.08‐3.40), pregnancy‐induced hypertension (RR 2.13; 95% CI, 1.26‐3.62), and postpartum haemorrhage (RR 1.22; 95% CI, 1.00‐1.49). Additionally, women with obesity had also higher risk of either elective (RR 2.40; 95% CI, 1.88‐3.06) or emergency (RR: 1.53; 95% CI, 1.34‐1.75) caesarean delivery. Conclusion: Maternal obesity is an emerging health problem in Tanzania. This study clearly demonstrates an association between increased risk of intrapartum complications and obesity. A review of guidelines around ANC screening and intrapartum care practices considering BMI, as well as appropriate messages for women with obesity, should be considered to improve maternal and newborn outcomes.